CHEMOTHERAPY IN COMBINED MODALITY TREATMENT FOR LOCALLY ADVAMCED NON-SMALL CELL LUNG CANCER - Е. L. Yumov; S. V. Miller; N. V. Litvyakov; Т. V. Polischuk; S. А. Tuzikov; О. V. Cheremisina; V. Е. Goldberg; Е. О. Rodionov (Сибирский онкологический журнал, 2016)
The comparative analysis of immediate and long-term clinical outcomes in 68 patients with stage III non-small cell lung cancer was carried out. The study group comprised 36 patients who received 2 cycles of neoadjuvant vinorelbin/carboplatin-containing chemotherapy with subsequent assessment of objective response. If complete and partial responses were achieved and in cases with stable disease, patients underwent radical surgery followed by 3 cycles of the same regimen of adjuvant chemotherapy. The control group consisted of 32 patients who underwent surgery alone. The results obtained showed efficacy of the combined modality treatment due to significant decrease in the rate of local recurrences, distant metastases and increase in the rate of overall survival as compared to the group with surgery alone.